ANALISIS PREFERENSI DAN KEPUASAN KONSUMEN KERIPIK PISANG SHINTA DI KOTA BANDAR LAMPUNG - Khister Praja Putra; Fembriarti Erry Prasmatiwi; Novi Rosanti (Lampung University, 2023)
This study aims to analyze preferences, consumption patterns and consumer satisfaction in purchasing Shinta Banana Chips in Bandar Lampung City. Respondents were taken by the accidental sampling method as many as 50 respondents and data collection was carried out from May to June 2022. The analytical method used is conjoint analysis, qualitative descriptive analysis, Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The result showed that the consumers of Shinta Banana Chips were mostly female aged 18-25 years as many as 26 consumers. The attributes of banana chips that became consumer preferences were sweet taste with a size of 250 grams, crunchy textured with plastic packaging. Shinta Banana Chips consumers usually buy and consume 250 grams of Banana Chips as many as 34 respondents (68%). The average purchase of 200-750 grams was 27 respondents with the frequency of purchasing Shinta Banana Chips at most 1-2 times per month (78%). The variation of the Shinta Banana Chips taste that many consumers like is the chocolate flavor variation (30%) with the reason that consumers consume it for their own consumption. Halal label is considered very important (86%). Consumer satisfaction was obtained by 86.41% in the very satisfied category. Key words: banana chips, consumer, consumption pattern, preference